APPLICATION OF HIGHER MATHEMATICS TO CHEMISTRY: MODELING REACTION RATE USING DIFFERENTIAL EQUATIONS (Modern American Journal of Engineering, Technology, and Innovation, 2025)
The article examines the application of higher mathematics to practical, in particular chemical processes, how to model the rate of a chemical reaction using differential equations, and reveals their meaning.